Revitalization of "Gotong Royong" as Social Capital in Village Infrastructure Development: A Case Study of Macadam Road Construction in Ngranget Village, Dagangan District, Madiun Regency - Aulia Zalzabela Widiyaningsih; Edy Prayitno; Mai Puspadyna Bilyastuti (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study examines the implementation of cooperation in the construction of macadam roads in Ngranget Village, Dagang District, Madiun Regency. Through participant observation and in-depth interviews, this study analyzes how the value of cooperation functions as social capital, strengthening community participation and collaborative village governance. The findings show that cooperation is not only a mechanism for resource mobilization but also an instrument for strengthening community capacity to achieve sustainable development. Gotong royong reflects the values of unity and social justice that underpin people's lives in Indonesia. This study emphasizes the relevance of local values in the context of Sustainable Development Goals (SDGs) 11 and 16. It shows that revitalizing cooperation is an effective strategy for realizing inclusive, sustainable, and equitable village development and provides an empirical basis for developing empowerment programs that place the community as the leading actor in development by strengthening village social capital in a more community-based manner.